Inclusive Entrepreneurship Infrastructure Development Special Aspects in Ukraine - Skrylnik, Andrey; Valiavskiy, Sergii; Voloshina, Oksana (International Journal of Engineering and Technology, 2018)
The purpose of the scientific article was to formulate a model for the infrastructure developmentÂ for inclusive entrepreneurship in Ukraine. For this purpose, the approaches of domestic scientists and practitioners concerning typology and identification of the main features and functions of inclusive entrepreneurship are generalized. It has been determined that inclusive development of entrepreneurship in contemporary conditions is considered as a policy for ensuring the possibility of starting their own business or self-employment for all groups of the population. The world experience of the inclusive entrepreneurship formation and development is generalized and the main factors hindering the activation of inclusive entrepreneurship in Ukraine at micro and macro levels are revealed. The funding sources structuring for inclusive entrepreneurship development at the territorial level was carried out. Â European models adaptation development problem of inclusive entrepreneurship in Ukraine for various social groups of the population is explored. Certain proposals for the implementation of vectors development inclusive enterprise, architectural, construction, financial, economic and social are formulated. Practical recommendations are developed, which will promote the development of inclusive business systems and improve the access of society all members to economic benefits, through the establishment of their own business or employment.Â Â